Event-free Survival in Patients with Chronic Myeloid Leukemia Receiving Front-line Imatinib Mesylate - Eyüpoğlu, Nesrin Damla; Çınar, Olgu Erkin; Aksu, Salih; Büyükaşık, Yahya; Sayınalp, Nilgün; Demiroğlu, Haluk; Göker, Hakan; Özcebe, Osman İlhami; Haznedaroğlu, İbrahim C. (Acta Medica, 2022)
Objective: Chronic myeloid leukemia (CML) prognostication at the time of diagnosis is critical to determine the intensity of initial treatment. Event-free survival (EFS) has become a prominent concept of prognosis in the patients with chronic phase CML (CML-CP). The aim of this study is to assess the prognostic impact of bone marrow (BM) and peripheral blood (PB) cellular components, in correlation with the clinical parameters. Materials and Methods: One hundred forty-three patients with CML-CP on the front-line imatinib mesylate therapy were recruited into this study. Clinical and laboratory characteristics, therapeutic responses were recorded. Sokal, Euro/Hasford, The EUropean Treatment Outcome Study (EUTOS) and The EUTOS long-term survival (ELTS) scores were calculated for the studied patients. Results: Median follow-up time was 84 (IQR: 54-125) and median front-line therapeutic duration was 56 (IQR:23-89) months. Five-year EFS rate was 62.3% (95% CI: 53.9-70.7). The blast percentage in the BM, EUTOS scores, and basophil percentage in PB were related with the poor therapeutic outcomes in frontline therapy (p=0.002, p=0.002 and p=0.042, respectively). Although Sokal risk classification showed that the intermediate class had a higher event risk compared to the low-risk class (p=0.001), the predictive association disappeared in high-risk classes. Conclusion: EUTOS score system has better predictive capability for front-line imatinib therapy comparing with other indices. Higher blast percentage in BM and increased basophil percentage in PB are independent risk factors, adversely related with EFS in patients with CML.